Development of metal silicides for deep submicron polycrystalline silicon gate - Pang, Chong Hau (2008)
Metal silicides are used to reduce the polycrystalline silicon (polysilicon) gate and contact resistances during fabrication of transistors in microelectronics devices. Generally, Titanium disilicides and Cobalt disilicides are widely utilized on transistors while Nickel monosilicides (NiSi) are still under intense investigation for future transistor technology. However, reactions between parent metals (Ti, Co and Ni) and silicon often present many different problems during silicides formation.